Tracked Changes. Connector sets and interconnect components to be used in optical fibre communication systems. Product specifications. Simplex and duplex cords made from simplex plugs with cylindrical ferrules, using EN 60793-2-50 single-mode B-652 ou B-657 fibre for Category C according to EN 61753-1 Part 14-1, (1st June 2023) - British Standards Institution,
No abstract available